2013
DOI: 10.1161/jaha.113.000097
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Stress Echocardiography Pattern for Myocardial Bridge With Invasive Structural and Hemodynamic Correlation

Abstract: BackgroundPatients with a myocardial bridge (MB) and no significant obstructive coronary artery disease (CAD) may experience angina presumably from ischemia, but noninvasive assessment has been limited and the underlying mechanism poorly understood. This study seeks to correlate a novel exercise echocardiography (EE) finding for MBs with invasive structural and hemodynamic measurements.Methods and ResultsEighteen patients with angina and an EE pattern of focal end‐systolic to early‐diastolic buckling in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 16 publications
1
67
0
Order By: Relevance
“…This suggests that cardiologists should consider the possibility of coronary spasm in patients with chest pain and MB on coronary angiograms. Several methods have been used to assess MB-related myocardial ischemia due to mechanical compression of the coronary artery by MB, such as pharmacological stress echocardiography [26] , stress myocardial perfusion imaging [27] , intracoronary blood flow velocity measurements [21,26] , and intracoronary pressure measurements [1,21,26,28] . In the current case, we assessed intracoronary pressure using a pressure wire because this technique has a reliable cutoff value [29] and can be used conveniently in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that cardiologists should consider the possibility of coronary spasm in patients with chest pain and MB on coronary angiograms. Several methods have been used to assess MB-related myocardial ischemia due to mechanical compression of the coronary artery by MB, such as pharmacological stress echocardiography [26] , stress myocardial perfusion imaging [27] , intracoronary blood flow velocity measurements [21,26] , and intracoronary pressure measurements [1,21,26,28] . In the current case, we assessed intracoronary pressure using a pressure wire because this technique has a reliable cutoff value [29] and can be used conveniently in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…the MB segment is present even at baseline [21] , only during pharmacological stress [1,26,28] , only within the MB segment [26] , or both within and beneath MB [1,21,28] . These different results may have been due to differences in the severity and degree of the MB itself as well as differences in the methods used to measure intracoronary pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An MB has traditionally been considered a benign condition because contraction of the bridging muscles alters blood flow within the underlying LAD during systole, whereas coronary flow in the LAD occurs predominantly in diastole. A number of studies, however, have indicated that an MB can lead to significant clinical symptoms, arrhythmia, or adverse cardiac events (ie, myocardial ischemia,4, 5 myocardial infarction,6 and sudden death7) in a subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of people with a bridge are asymptomatic, but a small subset of patients develop angina, likely secondary to dynamic ischemia in the myocardial territory of septal branches embedded within the bridged segment. 1 Symptoms may develop or progress with the patient's age, because of associated conditions such as endothelial dysfunction, diastolic dysfunction and ventricular hypertrophy. 2 In addition, atherosclerotic plaque can accumulate proximal to the MB, possibly from dynamic retrograde flow in the LAD resulting from compression of the bridged vessel segment.…”
mentioning
confidence: 99%